Experiences of the family caregiver of a person with intestinal ostomy due to colorectal cancer - Gláucia Sousa Oliveira; Marina Bavaresco; Cibelle Barcelos Fillipini; Sara Rodrigues Rosado; Eliza Maria Rezende Dázio; Silvana Maria Coelho Leite Fava (Rev Rene)
This is a study with the objective to know the experiences of the family caregiver of a person with intestinal ostomy due to colorectal cancer. A qualitative research, grounded on the humanization referential, made in 2013, through serialized semi-structured interviews and inductive analysis. It was approved by the Ethics and Research Committee under legal opinion no. 237,771. Seven family caregivers participated in this study in a county of southern Minas Gerais state, Brazil. Three categories emerged from the data: Relation with the disease and its treatments; Impact facing treatment and rehabilitation and Nets of support. The representation of the disease associated to finitude is reaffirmed. In order to lessen anguish and suffering, the family caregivers search support, mainly in spirituality. The impact resulting from the illness and the rehabilitation process imposes a new order to the caregivers, with personal and social renouncing, which provides a closer and more dedicated relation with the patient.